Peran Stres Kerja Dalam Memediasi Pengaruh Beban Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada CV. Bumi Mandiri Indonesia - Ragilita Aisya, Rizqi; Dian Evasari, Aprilia (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2023)
The aim of this study is to examine the role of work stress in mediating the effect of workload and work environment on employee performance at CV. Bumi Mandiri Indonesia. This study uses three kinds of variable, there are independent variable, dependent variable and intervening variable. the independent variables is workload and work environment and dependent variable is employee performance and the intervening variable is work stress. The samples of this study were employees of CV. Bumi Mandiri Indonesia. The data obtained through questionnaires, observations and interviews. The sampling technique was done by purposive sampling method. The analysis technique uses a measurement model or outer model, structural model or inner model, and hypothesis testing. The results of this study indicate that workload partially has a positive and significant effect on employee performance. The work environment partially has a negative and insignificant effect on employee performance. Work stress partially has a positive and significant effect on employee performance. Workload partially has a positive and insignificant effect on work stress. The work environment partially has a positive and significant effect on work stress. Workload partially has a positive and insignificant effect on employee performance mediated by work stress. This study shows that work stress cannot mediate the relationship between workload and employee performance. But work stress can mediate the relationship between the work environment and employee performance.